The Comprehensive Guide to NFTs, Digital Artwork, and Blockchain Technology - Beckman, Marc (New York Skyhorse, 2021)
Non-fungible tokens, or NFTs, are the most important digital innovation since the creation of blockchain and cryptocurrency. NFTs share the best elements of both of these, while also representing an entirely new step forward for technology. But how did NFTs arise, how will they impact art and business in the decades to come, and—perhaps most importantly—how can savvy entrepreneurs position themselves today for success in the NFT-driven world of tomorrow? This guide by industry leader and entrepreneur Marc Beckman delves into the underpinnings of NFT technology in a way that makes the subject clear and comprehensible to the layman, while drawing on Marc’s branding experience to explore exactly how NFTs are poised to change fashion, sport, fine art, and even social justice. In this book he explores how NFTs will create entirely new asset classes and investment possibilities, such as fractional ownership in dynamic works of art. And in doing so, he also tells the story of how he personally discovered and became entranced by this powerful new tool, and where he believes NFTs will take business and branding throughout the 21st century.
Keywords: Technology; Economy; Digital art